2022
DOI: 10.33487/edumaspul.v6i2.4562
|View full text |Cite
|
Sign up to set email alerts
|

Technological Knowledge (TK) of Elementary School Teacher Education Program Students in Elementary Science Learning

Abstract: Teaching is a component of the success of education. Technological knowledge (TK) or technological knowledge, which is one of the frameworks of technological pedagogical content knowledge (TPACK), is knowledge that students possess in order to be able to transmit or impart content to facilitate understanding for students. The aim of this study was to identify the kindergarten students of prospective primary school teachers in elementary science learning. This study uses a descriptive type of research with a qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…Previous research conducted on an elementary school teacher's pedagogical practices in teaching science materials revealed that the teacher's Pedagogical Content Knowledge (PCK) category was classified as "Pre-PCK" or in a lower category [13]. This indicates that teachers have not yet fully grasped the approach of integrating pedagogical knowledge and content knowledge in their teaching methods.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research conducted on an elementary school teacher's pedagogical practices in teaching science materials revealed that the teacher's Pedagogical Content Knowledge (PCK) category was classified as "Pre-PCK" or in a lower category [13]. This indicates that teachers have not yet fully grasped the approach of integrating pedagogical knowledge and content knowledge in their teaching methods.…”
Section: Introductionmentioning
confidence: 99%